Cerumenogram as an assay for the metabolic diagnosis of precancer, cancer, and cancer remission - João Marcos Gonçalves Barbosa; Camilla Gabriela de Oliveira; Marina Ferraz Gontijo Soares; Larissa Fernanda Medeiros Vieira; Omar Carneiro Filho; Daniela Medeiros Milhomem Cardoso; Patricia Medeiros Milhomem Beato; Cristina Aparecida Trigo Martins Moro; Anselmo Elcana de Oliveira; Nelson Roberto Antoniosi Filho (Scientific Reports)
Abstract Early diagnosis is crucial for successful cancer treatment. As a mitochondrial metabolic disease, cancer produces volatile organic metabolites that are present in earwax, allowing differentiation between healthy individuals and those with cancer through an assay called cerumenogram. In this case series study, we demonstrated that this assay also enables the diagnosis of precancerous stages, such as hypermetabolic inflammation and dysplasia, which can aid in treatments to prevent cancer progression. Additionally, this assay reveals that oncological metabolism differs from that observed in metaplasias, cysts, and benign tumors, helping to avoid unnecessary oncological procedures due to suspected malignancy. Cerumenogram can also be used to assess cancer remission. Thus, the cerumenogram emerges as an assay that might enable the diagnosis of cancer, monitor remission, and identify precancerous stages, covering key steps of tumorigenesis.